2014
DOI: 10.1371/journal.pone.0093895
|View full text |Cite|
|
Sign up to set email alerts
|

Zinc, Iron, Manganese and Copper Uptake Requirement in Response to Nitrogen Supply and the Increased Grain Yield of Summer Maize

Abstract: The relationships between grain yields and whole-plant accumulation of micronutrients such as zinc (Zn), iron (Fe), manganese (Mn) and copper (Cu) in maize (Zea mays L.) were investigated by studying their reciprocal internal efficiencies (RIEs, g of micronutrient requirement in plant dry matter per Mg of grain). Field experiments were conducted from 2008 to 2011 in North China to evaluate RIEs and shoot micronutrient accumulation dynamics during different growth stages under different yield and nitrogen (N) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 36 publications
13
36
0
Order By: Relevance
“…It suggests that application of fertilizers and manure either alone or in combination promoted the uptake of Zn by rice. It was reported that proper levels of N and K could enhance the uptake of Zn by rice; our results were in agreement with earlier reports (Li et al 2007;Dash et al 2010;Rutkowska et al 2014;Xue et al 2014). However, wherever phosphatic fertilizers have been applied, the corresponding increase in the Zn uptake over the control was less as compared to the treatments where phosphatic fertilizer was not used.…”
Section: Uptake Of Micronutrients By Ricesupporting
confidence: 94%
See 1 more Smart Citation
“…It suggests that application of fertilizers and manure either alone or in combination promoted the uptake of Zn by rice. It was reported that proper levels of N and K could enhance the uptake of Zn by rice; our results were in agreement with earlier reports (Li et al 2007;Dash et al 2010;Rutkowska et al 2014;Xue et al 2014). However, wherever phosphatic fertilizers have been applied, the corresponding increase in the Zn uptake over the control was less as compared to the treatments where phosphatic fertilizer was not used.…”
Section: Uptake Of Micronutrients By Ricesupporting
confidence: 94%
“…Application of chemical fertilizers although increased the Cu uptake, but the balanced fertilization (NPK) resulted in higher uptake. Earlier authors have reported that balanced fertilization not only increases grain yield and maintains soil nutrient balance, but also accelerates rice nutrient uptake (Mann et al 2006;Li et al 2007;Xue et al 2014). Similar findings were reported by Aulakh and Malhi (2005) who enumerated that the interaction of other soil macronutrients and micronutrients also affected micronutrient uptake by crops.…”
Section: Uptake Of Micronutrients By Ricesupporting
confidence: 69%
“…Potassium (K) was extracted by NH 4 OAc and determined at flame photometer (Van Reeuwijk 1992). Micro-minerals (Cu, Fe, Mn and Zn) were extracted with DTPA (diethylenetriaminepentaacetic acid) solution (Lindsay and Norvell 1978) and served for concentration measurement by Inductively Coupled Plasma Optical Emission Spectrometer (ICP-OES, Perkin-Elmer, USA) (Xue et al 2014).…”
Section: Plant Materials and Field Designmentioning
confidence: 99%
“…The analysis methods used are almost identical to those described by Xue et al (2014). At harvest, five plants were chosen from the middle of each row for trait evaluation.…”
Section: Phenotyping For Quality Traitsmentioning
confidence: 99%
“…Competition for nutrients may even occur between different weeds, which can determine the composition of the weed community (Tilman et al 1999). The necessity of metal micronutrients supply for maximum maize yield has been documented (Salem & El-Gizawy 2012;Bender et al 2013;Xue et al 2014). Information on the relationships between metal micronutrients in weeds and main crops is scarce.…”
Section: Introductionmentioning
confidence: 99%